Numerical study of defect localization in additive manufactured short fiber reinforced composites with diffuse ultrasonic wave inspection - Peng, Yue; Xu, Hongxuan; Sun, Jingguo; Zuo, Jiancun; Zhu, Qi (Frontiers in Physics, 2022)
The structures of short fiber reinforced composites become designable from macroscopic to microscopic due to the advancement in additive manufacturing technologies. The diffuse ultrasonic wave inspection benefits from information from multiple scattering processes, which is suitable for the quality assurance of complex structures. This study established a two-dimensional wave propagation model assuming the decoupling of the fiber volume into the fiber distribution matrix in the plane and the local fiber fraction along the thickness axis. The k-space pseudospectral method was applied to calculate the diffuse wave fields. The defect inspection process was studied numerically based on the Locadiff technique for additive-manufactured short-fiber reinforced composites. The stretching method provided the same average distance but a smaller relative deviation to the defect than the doublet method. The localization resolution improved significantly for the initial increment of the number of transmitters; limited improvement can be achieved further. Localization results fluctuated when the transmitter combination groups were distant from the defect. This method worked well with the isotropic and quasi-isotropic plates, while an oversimplification was found for the unidirectional fiber structure.